Methodological Approaches to the Formation of the Quality Management System for Hotels in Russian Federation - Sergey Sergeevich Skobkin; Yana Andreevna Belavina; Kalita Gleb Vadimovich (International Review of Management and Marketing, 2017)
The purpose of this article is to develop managerial methods of effective hotel operation in order to improve competitiveness on the basis of quality management. The current economic situation is characterized by significant changes in the behavior of the world markets, which entails the need to adapt to the new situation. In this situation, one of the necessary conditions for the formation of positive dynamics of the development of hospitality industry in Russian Federation is the creation and implementation of The Quality Management System (QMS) for hotels, which is the aim of this research work. Authors propose to achieve this goal by solving following tasks: i) to improve management activities of enterprises in hospitality industry in order to increase their competitiveness; ii) to develop QMS, which can serve as a basis of appropriate management model of enterprises in hospitality industry; iii) to propose effective quality control methods in hotel operations. An important role in this context is given to effective management, which ensures the necessary conditions for the formation of services that represent value to the consumer.